ICESsuHN105, a Novel Multiple Antibiotic Resistant ICE in Streptococcus suis Serotype 5 Strain HN105 - Zhu, Yinchu; Zhang, Yue; Ma, Jiale; Dong, Wenyang; Zhong, Xiaojun; Pan, Zihao; Yao, Huochun (Frontiers in Microbiology, 2019)
Streptococcus suis serotype 5, an emerging zoonosis bacterial pathogen, has been isolated from infections in both pigs and humans worldwide. In this study, we sequenced the first complete genome of a virulent, multi-drug resistant SS5 strain HN105. The strain HN105 displayed enhanced pathogenicity in zebrafish and BABL/c mouse infection models. Comparative genome analysis identified a novel 80K integrative conjugative element (ICE), ICESsuHN105, as required for the multi-drug resistance phenotype. Six corresponding antibiotic resistance genes in this ICE island were identified, namely tet (O), tet (M), erm (two copies), aph, and spc. Phylogenetic analysis classified the element as a homolog of the ICESa2603 family, and contained the typical family backbone and insertion DNA. DNA hybrids mediated by natural transformation between HN105 and ZY05719 verified the antibiotic resistant genes of ICESsuHN105 that could be transferred successfully, while were dispersedly inserted with a single gene in different genomic locations of ZY05719(HN105) transformants. To further identify the horizontal transfer of ICESsuHN105 as a whole mobile genetic element, a circular intermediate form of ICESsuHN105 was detected by PCR. However, the effective conjugation using serotype 2 S. suis as recipients was not observed in current assays in vitro. Further studies confirmed the presence of the complete lantibiotic locus encoded in ICESsuHN105 that effectively inhibits the growth of other streptococci. In summary, this study demonstrated that antibiotic resistance genes in ICE that are able to transfer between different clinical isolates and adapt to a broader range of Streptococcus serotype or species.